An Ion‐Dipole‐Reinforced Polyether Electrolyte with Ion‐Solvation Cages Enabling High–Voltage‐Tolerant and Ion‐Conductive Solid‐State Lithium Metal Batteries (Adv. Funct. Mater. 5/2022). (25th January 2022) - Zhang, Kun; Wu, Feng; Wang, Xinran; Zheng, Lumin; Yang, Xiaoyu; Zhao, Huichun; Sun, Yuheng; Zhao, Wenbin; Bai, Ying; Wu, Chuan
Abstract : High‐Performance Polymer Electrolytes In article number 2107764, Xinran Wang, Ying Bai, Chuan Wu, and co‐workers develop a hyperbranched polyether electrolyte for solid‐state Li metal batteries. The existing ion‐solvation structures allow for fast Li + migration (1.26 × 10 −4 S cm −1, 25 °C), a wide stable voltage window (up to 4.6 V), and Li dendrite suppression, overcoming the insufficiencies encountered by polymer electrolytes. The ion‐dipole‐reinforced solid electrolyte yields sustainable Li stripping/platting and interfacial stability, thus enabling high cycle stability and capacity retention in NCM811 |Li solid‐state cells.